Aqueous Extract of Descuraniae Semen Attenuates Lipopolysaccharide-Induced Inflammation and Apoptosis by Regulating the Proteasomal Degradation and IRE1α-Dependent Unfolded Protein Response in A549 Cells - Hsieh, Po-Chun; Peng, Chung-Kan; Liu, Guan-Ting; Kuo, Chan-Yen; Tzeng, I-Shiang; Wang, Ming-Chieh; Lan, Chou-Chin; Huang, Kun-Lun (Frontiers in Immunology, 2022)
Background: Lipopolysaccharide (LPS)-induced acute lung injury (ALI) induces endoplasmic reticulum stress, unfolded protein response (UPR), apoptosis, and inflammation. Inositol-requiring enzyme 1 (IRE1)-α is important for adaptive and apoptotic UPR determination during ER stress. The aqueous extract of Descuraniae Semen (AEDS) is reported to be a safe and effective herb for the treatment of pulmonary edema as it shows anti-inflammatory activities. Methods: We investigated the effects of AEDS on LPS-induced ALI in A549 cells with respect to the regulation of IRE1α-dependent UPR, proteasomal degradation, mitochondrial membrane potential (MtMP), inflammation, and apoptosis. Results: AEDS attenuated ER stress by regulating the proteasomal degradation. LPS induced ER stress (binding immunoglobulin protein [BiP], phosphorylated IRE1α, sliced X-box binding protein 1 [XBP1s], phosphorylated cJUN NH2-terminal kinase [pJNK], B-cell lymphoma [Bcl]-2-associated X [Bax], Bcl-2), inflammation (nucleus factor-kappa B [NF-κB] p65 nuclear translocation, nucleus NF-κB, pro-inflammatory cytokines) and apoptosis (C/EBP homologous protein [CHOP], cytochrome c, caspase-8, and caspase-6, and TUNEL) were significantly attenuated by AEDS treatment in A549 cells. AEDS prevents LPS-induced decreased expression of MtMP in A549 cells. Conclusions: AEDS attenuated LPS-induced inflammation and apoptosis by regulating proteasomal degradation, promoting IRE1α-dependent adaptive UPR, and inhibiting IRE1α-dependent apoptotic UPR. Moreover, IRE1α-dependent UPR plays a pivotal role in the mechanisms of LPS-induced ALI. Based on these findings, AEDS is suggested as a potential therapeutic option for treating patients with ALI.